Analyzing the Elements and Ramifications of Substance Abuse among Secondary School Students: A Case of Six Selected Secondary Schools in Chibombo District of Central Province, Zambia. (International Journal of Scientific Research and Management (IJSRM), 2024)
: This research examining the factors and consequences of drug abuse among secondary school pupils: a case of six selected secondary schools in Chibombo district of central province, Zambia. The study aimed at shedding light on the underlying factors contributing to drug abuse and its impact on the pupil’s population. The study used both qualitative and quantitative methods; empirical data was collected from pupils, teachers, school head teachers and education officer through questionnaire guides. The researcher used purposive and simple random sampling, whereby the researcher selected 200 respondents as drowned out from the research population; this included 2 officers from the ministry of education, 6 head teachers, 60 teachers and 132 pupils in six selected secondary schools in Chibombo district of Central province, Zambia. The data which was collected was analysed using Microsoft Excel and SPSS version 25 to produce outputs according to the research objectives. Therefore, the study found out that the burden of substance abuse is still high in our study population and the prevalence was significantly higher among students who had not received any formal teachings on the subject. It therefore becomes imperative to incorporate teachings on substance abuse into the national school curriculum for secondary school students. The National School Health Policy needs to be expanded to incorporate this vital issue. The law enforcement agents regulating drug trafficking in and out of Zambia should begin to beam their search lights on secondary school students.